An Evaluation on Attitudes of Students, Receiving English Preparatory Education, towards English Course - Tuncer, Murat; Temur, Mehmet (Murat TUNCER, 2018)
The main aim of this research is to evaluate the attitudes of students, receiving English Preparatory Education (EPE), towards English courses. This work was carried out based on survey research model. According to the findings gained by means of discriminant analysis, we can make a collocation among learners’ attitudes depending on their income levels that were displayed in portional of horizontal average as low, middle and high. In particular, it was reached with figure %52,3 among the learners whose income level was illustrated as middle. Finally, when the attitudinal descriptive measure instrument was put into consideration during the educational- teaching proccesses, we can suggest an other more functional measuremental instrument that can be used instead of attitunal, or that’s to say, it can be concluded that there is an other variance which can better percieve income measurement to collocate the findings in more correct figures %52,3 of research.

Bu araştırmanın genel amacı, İngilizce hazırlık eğitimi alan öğrencilerin İngilizce derslerine yönelik tutumlarını değerlendirmektir. Araştırma tarama modeline göre yürütülmüştür. Diskriminant analizi ile elde edilen bulgulara göre, öğrencilerin düşük, orta ve yüksek olarak algıladıkları gelir durumları ile onların tutumları arasında bir ilişki kurabiliriz. Özellikle gelir düzeyini orta olarak belirten öğrenciler açısından % 52,3'lük bir sınıflama oranına ulaşılmıştır. Sonuç olarak, eğitim-öğretim süreçlerinde tutumu diğer değişkenlere nazaran tanımlayıcı bir değişken olarak önerebiliriz. Gelir durumu İngilizce dersine yönelik tutumu % 52,3 oranında, yüksek bir varyansla açıklamaktadır.
Hazırlık Eğitimi Alan Öğrencilerin İngilizce Dersine Yönelik Tutumlarının Değerlendirilmesi
Keywords: Studies on Education; Eğitim Üzerine Çalışmalar